Purification, characterization and thermal inactivation kinetics of a non-regioselective thermostable lipase from a genotypically identified extremophilic Bacillus subtilis NS 8. - Olusesan, Akanbi Taiwo; Kamaruzaman, Azura Liana; Forghani, Bita; Abu Bakar, Fatimah; Mohammed, Abdulkarim Sabo; Radu, Son; Abd. Manap, Mohd. Yazid; Saari, Nazamid (Elsevier, 2011)
Thermostable lipase produced by a genotypically identified extremophilic Bacillus subtilis NS 8 was purified 500-fold to homogeneity with a recovery of 16% by ultrafiltration, DEAE-Toyopearl 650M and Sephadex G-75 column. The purified enzyme showed a prominent single band with a molecular weight of 45 kDa. The optimum pH and temperature for activity of lipase were 7.0 and 60°C, respectively. The enzyme was stable in the pH range between 7.0 and 9.0 and temperature range between 40 and 70°C. It showed high stability with half-lives of 273.38 min at 60°C, 51.04 min at 70°C and 41.58 min at 80°C. The D-values at 60, 70 and 80°C were 788.70, 169.59 and 138.15 min, respectively. The enzyme's enthalpy, entropy and Gibb's free energy were in the range of 70.07–70.40 kJ mol−1, −83.58 to −77.32 kJ mol−1 K−1 and 95.60–98.96 kJ mol−1, respectively. Lipase activity was slightly enhanced when treated with Mg2+ but there was no significant enhancement or inhibition of the activity with Ca2+. However, other metal ions markedly inhibited its activity. Of all the natural vegetable oils tested, it had slightly higher hydrolytic activity on soybean oil compared to other oils. On TLC plate, the enzyme showed non-regioselective activity for triolein hydrolysis.